What every engineer should know about microcomputers hardware/software design, a step-by-step example - Bennett, William S. (What every engineer should know, 1991)
Revised and expanded guide demonstrates microcomputer usage by working through one simple design challenge and explaining its solution. This edition features the contributions of an Ada expert, demonstrates (in 14 new chapters) the development of a microcomputer system structured by this language, and stronly emphasized its advantages, including the ability to conveniently isolate functions or make changes more quickly in an application.